High-strength controllable phase change stainless steel wire and manufacturing method thereof
By adjusting the chemical composition and process flow of stainless steel wire, the problems of quality consistency and performance stability of stainless steel wire in the prior art are solved, and high-strength and high-consistency stainless steel wire materials are achieved, meeting the application needs of high-end fields.
Patent Information
- Application Number
- CN202411664447.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-03-04
Smart Images

Figure CN119553186A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of stainless steel wire preparation, and in particular to a high-strength controllable phase-change stainless steel wire and a manufacturing method thereof. Background Art
[0002] 0Cr17Ni7Al is a controllable phase change stainless steel with high medium temperature strength (not higher than 350°C) and corrosion resistance. It is often used to prepare plates for applications in marine atmospheric environments, as well as spring wires for applications in aviation, aerospace and other fields.
[0003] At present, the preparation of 0Cr17Ni7Al spring wire is mainly through cold drawing, which has high mechanical properties, such as strength. The composition of 0Cr17Ni7Al stainless steel is in the boundary area of ferrite-austenite-martensite in the thermodynamic phase diagram. A slight fluctuation in the composition will lead to huge differences in the content of delta ferrite, phase transition point, and mechanical properties. When using the existing technology to produce wires according to the same drawing process, it is difficult to produce wires of consistent quality. The organization and performance of wires in different batches vary greatly, and the size and elastic performance qualification rate of the springs cannot be effectively guaranteed. It is difficult to stably meet the application requirements of high-end fields such as aviation and aerospace for high-performance wires in multiple batches and specifications, which seriously limits the mass application of wires.
[0004] Therefore, there is an urgent need for a wire material with stable quality and good consistency during mass production, and whose strength and elastic properties meet the use requirements. Summary of the invention
[0005] In view of the above analysis, the present invention aims to provide a high-strength controllable phase-change stainless steel wire and a manufacturing method thereof, which can achieve stable quality and good consistency during mass production of the wire, and whose strength and elastic properties meet the use requirements.
[0006] On the one hand, the present invention provides a high-strength controllable phase-change stainless steel wire, whose chemical composition, by weight percentage, includes C≤0.09%, Si≤1.00%, Mn≤1.00%, P≤0.04%, S≤0.030%, Ni: 7.25%~8.00%, Cr: 16.00%~18.00%, Al: 0.50%~0.75%, Mo: 0.20%~0.60%, Cu: 0.50%~1.0%, N: 0.01%~0.10%, Co: 0.10%~0.50%, and the balance is Fe and unavoidable impurities.
[0007] Furthermore, the chemical composition of the stainless steel wire includes, by weight percentage, C≤0.09%, Si≤1.00%, Mn≤1.00%, P≤0.04%, S≤0.030%, Ni: 7.85%~8.00%, Cr: 16.00%~18.00%, Al: 0.50%~0.65%, Mo: 0.20%~0.60%, Cu: 0.70%~1.0%, N: 0.08%~0.10%, Co: 0.21%~0.50%, and the balance is Fe and unavoidable impurities.
[0008] Furthermore, the martensitic transformation point of the stainless steel wire is in the range of -20°C to 50°C.
[0009] Furthermore, the structure of the stainless steel wire is martensite and retained austenite.
[0010] Furthermore, the volume fraction of martensite is 75% to 100%; the volume fraction of delta ferrite is ≤1%.
[0011] On the other hand, the present invention provides a method for manufacturing high-strength controllable phase-change stainless steel wire, which comprises smelting, forging and rolling to obtain wire rods; subjecting the obtained wire rods to multiple rough drawing, intermediate annealing and finished product drawing to obtain stainless steel wires;
[0012] The surface reduction rate of the finished product drawn is 56% to 85%.
[0013] Furthermore, the intermediate annealing system is a 950°C to 1050°C solution water cooling treatment.
[0014] Furthermore, after solution cooling treatment at 950° C. to 1050° C., the volume fraction of austenite is ≥60%.
[0015] Furthermore, the specification of the wire is φ3.5mm, φ3.0mm or φ0.3mm.
[0016] Furthermore, the tensile strength of the stainless steel wire is above 1500 MPa, and the strength fluctuation Cv value is less than 3%.
[0017] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:
[0018] 1. The present invention increases Ni and Cu in the proportion of components, adds Co and N elements, increases the Ni equivalent of the material, expands the austenite phase region, and transfers from the boundary region of ferrite-austenite-martensite to the austenite + martensite phase region, thereby avoiding the formation of delta ferrite which has a greater impact on the structure and performance consistency of the wire material, and reduces the sensitivity of the structure to the composition and process;
[0019] 2. In the present invention, the range of Ms point is -20~50℃, which ensures that a large amount of austenite phase (volume fraction ≥ 60%) can be obtained after solution treatment, so that the material has a lower yield strength and higher plasticity, and has good drawing formability. Under the induction of drawing stress, the austenite phase undergoes martensitic transformation, which on the one hand improves the strength, and on the other hand plays a certain role in coordinating deformation, so that the material obtains high strength that meets the elastic limit requirements of the spring after cold drawing and aging treatment, and its tensile strength in the cold drawn state is above 1500MPa;
[0020] 3. In order to avoid the formation of delta ferrite, the present invention reduces the Al content, and its strengthening effect will decrease accordingly. In order to compensate for the strength reduction caused by the reduction of Al content, the Cu content is increased, and the strength after aging treatment is increased by precipitating Cu-rich nano-strengthening phase;
[0021] 4. The drawing plasticity of the wire material decreases with the increase of the drawing deformation, especially for ultra-fine wires with a specification of less than 1.0 mm. In order to meet the strength requirements, the drawing reduction rate is generally greater than 75%, which is very easy to break the wire. Adding a small amount of Co element has little effect on the mechanical properties, but it can change the strain hardening index, improve the drawing formability of the wire material, and avoid the phenomenon of wire breakage when drawing ultra-fine wires with a specification of less than 1.0 mm.
[0022] In the present invention, the above-mentioned technical solutions can also be combined with each other to achieve more preferred combination solutions. Other features and advantages of the present invention will be described in the subsequent description, and some advantages can become obvious from the description, or can be understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained through the contents particularly pointed out in the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] The drawings are only for the purpose of illustrating particular embodiments and are not to be considered limiting of the present invention. Like reference symbols denote like components throughout the drawings.
[0024] Figure 1 The metallographic image of the wire rod obtained in Example 1 of the present invention;
[0025] Figure 2 This is a metallographic diagram of the wire rod obtained in Comparative Example 1 of the present invention;
[0026] Figure 3 This is a metallographic diagram of a batch of Example 1 of the present invention;
[0027] Figure 4 This is the metallographic diagram of the second batch of Example 1 of the present invention;
[0028] Figure 5 The metallographic images of three batches of Example 1 of the present invention are as follows;
[0029] Figure 6 This is a metallographic diagram of a batch of Example 2 of the present invention;
[0030] Figure 7 This is a metallographic diagram of the second batch of Example 2 of the present invention;
[0031] Figure 8 The metallographic images of three batches of Example 2 of the present invention are as follows;
[0032] Fig. 9 This is a metallographic diagram of a batch of Example 3 of the present invention;
[0033] Fig.10 This is the metallographic diagram of the second batch of Example 3 of the present invention;
[0034] Fig.11 The metallographic images of three batches of Example 3 of the present invention are as follows;
[0035] Fig.12 This is the metallographic image of a batch of comparative example 1;
[0036] Fig.13 This is the metallographic image of the second batch of comparative example 1;
[0037] Fig.14 These are metallographic images of three batches of comparative example 1. DETAILED DESCRIPTION
[0038] The preferred embodiments of the present invention will be described in detail below in conjunction with the accompanying drawings, wherein the accompanying drawings constitute a part of the present invention and are used together with the embodiments of the present invention to illustrate the principles of the present invention, but are not used to limit the scope of the present invention.
[0039] 0Cr17Ni7Al is a controllable phase change stainless steel, which is often used to prepare plates for use in marine atmospheric environments and spring wires for use in aviation, aerospace and other fields.
[0040] Spring wire is mainly prepared by cold drawing. However, the composition of 0Cr17Ni7Al stainless steel is in the boundary region of ferrite-austenite-martensite in the thermodynamic phase diagram. A slight fluctuation in the composition will lead to huge differences in delta ferrite content, phase transition point, and mechanical properties. Therefore, when the same technology is used to produce wire, the organization and performance of different batches of wire vary greatly, which seriously limits the mass application of wire in order to stably meet the application requirements of high-performance wire in multiple batches and specifications in high-end fields such as aviation and aerospace.
[0041] Therefore, the present invention provides a high-strength controllable phase-change stainless steel wire, whose chemical composition, by weight percentage, includes C≤0.09%, Si≤1.00%, Mn≤1.00%, P≤0.04%, S≤0.030%, Ni: 7.25%-8.00%, Cr: 16.00%-18.00%, Al: 0.50%-0.75%, Mo: 0.20%-0.60%, Cu: 0.50%-1.0%, N: 0.01%-0.10%, Co: 0.10%-0.50%, and the balance is Fe and unavoidable impurities.
[0042] Compared with the prior art, the stainless steel wire provided by the present invention increases the Ni equivalent of the stainless steel wire and expands the austenite phase region by adding chemical elements and adjusting the content thereof. The composition of the stainless steel wire is transferred from the boundary region of the ferrite-austenite-martensite three regions to the austenite + martensite phase region; thereby avoiding the formation of delta ferrite which has a greater impact on the consistency of the wire structure and performance, reducing the sensitivity of the structure to the composition and process, and ultimately ensuring that the structure and performance of the stainless steel wire produced in different batches have little or no difference.
[0043] Specifically, the chemical composition of the stainless steel wire includes, by weight percentage, C≤0.09%, Si≤1.00%, Mn≤1.00%, P≤0.04%, S≤0.030%, Ni: 7.85%-8.00%, Cr: 16.00%-18.00%, Al: 0.50%-0.65%, Mo: 0.20%-0.60%, Cu: 0.70%-1.0%, N: 0.08%-0.10%, Co: 0.21%-0.50%, and the balance is Fe and unavoidable impurities.
[0044] It should be noted that, compared with 0Cr17Ni7Al stainless steel wire, in the chemical composition of the stainless steel wire of the present invention: the content of Ni element is maintained at 7.25% to 8.00%, maintained at a relatively high upper limit, preferably 7.85% to 8.00%. In order to avoid the formation of delta ferrite, the present invention keeps the content of Al element at 0.50% to 0.75%, preferably 0.50% to 0.65%. However, when the content of Al element is low, the strengthening effect will decrease accordingly, so the present invention increases the content of Cu, maintained at 0.50% to 1.0%, preferably 0.70% to 1.0%, and increases the strength of the stainless steel wire after aging treatment by precipitating a Cu-rich nano-strengthening phase.
[0045] In addition, C is an austenite-forming element, which can inhibit the precipitation of ferrite. The addition of a small amount of Mo element can further improve the tempering resistance of martensite laths, and can also improve corrosion resistance and high-temperature strength stability. Co and N elements are added to the composition of the stainless steel wire of the present invention, and their contents are controlled at 0.1% to 0.50% and 0.01% to 0.1%, respectively. Co and N elements can increase the Ni equivalent in the stainless steel wire and expand the austenite phase region; at the same time, Co element is an austenite-forming element, which can reduce the tendency of delta ferrite formation on the one hand, and on the other hand, adding an appropriate amount of Co element can change the strain hardening index, improve the drawing formability of the wire, and avoid the phenomenon of ultra-fine wire drawing fracture.
[0046] Specifically, the martensitic transformation point of the stainless steel wire is in the range of -20°C to 50°C.
[0047] Specifically, the structure of the stainless steel wire is martensite and retained austenite.
[0048] Specifically, the volume fraction of the martensite is 75% to 100%; the volume fraction of delta ferrite is ≤1%.
[0049] It should be noted that the range of Ms point is -20~50℃, which can ensure that a large amount of austenite phase (volume fraction ≥60%) is obtained after solution treatment, so that the material has a lower yield strength and higher plasticity, and has good drawing formability. Under the induction of drawing stress, the austenite phase undergoes martensitic transformation, which on the one hand improves the strength, and on the other hand plays a certain role in coordinating deformation, so that the material obtains high strength that meets the elastic limit requirements of the spring after cold drawing and aging treatment.
[0050] The present invention provides a method for manufacturing high-strength controllable phase-change stainless steel wire, which comprises smelting, forging and rolling to obtain a wire rod; subjecting the obtained wire rod to multiple rough drawing, intermediate annealing and finished product drawing to obtain the stainless steel wire;
[0051] The intermediate annealing is a solution water cooling treatment at 950°C to 1050°C;
[0052] The surface reduction rate of the finished product drawn is 56% to 85%.
[0053] Compared with the prior art, the present invention can ensure that the differences in the organization and performance of wires of different batches are small and the fluctuation Cv value is less than 3% through the interaction of components and manufacturing methods, and can also ensure that the wires have higher strength, especially tensile strength. The finished wire with a surface reduction rate of more than 56% has a tensile strength of more than 1500MPa in the cold-drawn state.
[0054] The manufacturing method obtains high-strength wire through the phase transformation strengthening effect of the strain-induced martensitic phase transformation produced by drawing and the superposition effect of the cold drawing hardening effect. In the present invention, the wire is formed by multiple cold drawing passes, and the intermediate wire in each pass needs to be solution annealed and softened, and the surface reduction rate of the finished product drawing pass is controlled at 56% to 85%.
[0055] Specifically, after solution cooling treatment at 950° C. to 1050° C., the volume fraction of austenite is ≥60%.
[0056] It should be noted that after obtaining the wire rod in the present invention, a solid solution treatment is required to obtain a large amount of austenite phase, the volume fraction of which is ≥60%, so that the wire rod has a lower yield strength and higher plasticity, good drawing formability, and ensures the formability of the cold drawing process, and is not easy to break. Under the induction of the drawing stress, the austenite phase undergoes a martensitic phase transformation, which on the one hand improves the strength, and on the other hand plays a certain role in coordinating deformation, so that the material obtains a high strength that meets the elastic limit requirements of the spring after cold drawing and aging treatment.
[0057] In the present invention, the solution treatment must be cooled by water cooling to ensure that the austenite phase is retained to room temperature and the martensite phase transformation does not occur prematurely. The martensite content of wires of different specifications is different. Generally, coarse wires contain less than 20% austenite, and ultra-fine wires are mostly full martensite structures.
[0058] Depending on the production line, the on-site production uses a low-temperature (950-1000°C) solution treatment for 1-4 hours in a box furnace, and the online treatment can use a high-temperature (1000-1050°C) solution treatment for 5-15 minutes to obtain similar strength and plasticity.
[0059] Specifically, the temperature of the aging heat treatment is 460-500° C., and the time is 1-2 hours.
[0060] It should be noted that in order to meet the requirements of high-performance springs for elastic limit, the finished product needs to be subjected to aging heat treatment after drawing, which can further improve the strength of the wire. The finished product drawing wire with a surface reduction rate of more than 56% can be increased to more than 1850MPa.
[0061] Specifically, the specification of the wire material may be φ3.5 mm, φ3.0 mm or φ0.3 mm.
[0062] In order to more clearly describe the present invention, it is further illustrated by the following examples and comparative examples.
[0063] Example 1
[0064] The manufacturing method of the stainless steel wire with a diameter of φ3.5 mm comprises the following steps:
[0065] S1: smelting, using 1T vacuum induction + electroslag remelting process to obtain a steel ingot, whose chemical composition is C: 0.07%, Si: 0.31%, Mn: 0.8%, P: 0.005%, S: 0.002%, Ni: 7.85%, Cr: 16.70%, Al: 0.70%, Mo: 0.40%, Cu: 0.70%, N: 0.08%, Co: 0.21%, and the balance is Fe;
[0066] S2: Forging and rolling, the steel ingot is heated at 1140℃ for forging and rolled into φ9.5mm wire rod;
[0067] S3: intermediate annealing, solution treatment at 1040℃ for 15min and water cooling, phase transition point Ms temperature is 29℃;
[0068] S4: The obtained wire rod is subjected to multiple rough drawing, intermediate annealing and finished product drawing;
[0069] φ9.5mm→Φ7.2mm→intermediate annealing→Φ5.6mm→intermediate annealing→Φ3.5mm; the surface reduction rate of the finished drawing is 60%; the intermediate annealing adopts 950℃ insulation for 2h, water cooling, and obtains cold-drawn wire.
[0070] Example 2
[0071] The preparation process of Example 2 is substantially the same as that of Example 1, except that in Example 2, a stainless steel wire with a diameter of φ3.0 mm is prepared. In step S4, φ9.5 mm→φ7.0 mm→intermediate annealing→φ5.1 mm→intermediate annealing→φ3.0 mm, and the surface reduction rate of the finished drawn product is 65.4%.
[0072] Example 3
[0073] The preparation process of Example 3 is substantially the same as that of Example 1, except that in Example 3, a stainless steel wire with a diameter of φ0.3 mm is prepared. In step S4, φ9.5 mm→φ7.0 mm→intermediate annealing→φ4.6 mm→intermediate annealing→φ2.3 mm→intermediate annealing→φ0.72 mm→intermediate annealing→φ0.3 mm, and the surface reduction rate of the finished drawing product is 82.6%.
[0074] Example 4
[0075] The preparation process of Example 4 is substantially the same as that of Example 1, except that the chemical composition in Example 4 is C: 0.09%, Si: 0.50%, Mn: 0.95%, P: 0.005%, S: 0.002%, Ni: 7.96%, Cr: 16.05%, Al: 0.50%, Mo: 0.40%, Cu: 0.90%, N: 0.02%, Co: 0.21%, and the balance is Fe.
[0076] Example 5
[0077] The preparation process of Example 5 is substantially the same as that of Example 2, except that the chemical composition of Example 4 in Example 5 is C: 0.09%, Si: 0.35%, Mn: 0.95%, P: 0.005%, S: 0.002%, Ni: 7.96%, Cr: 17.05%, Al: 0.50%, Mo: 0.40%, Cu: 0.90%, N: 0.02%, Co: 0.21%, and the balance is Fe.
[0078] Example 6
[0079] The preparation process of Example 6 is substantially the same as that of Example 3, except that the chemical composition of Example 4 in Example 6 is C: 0.09%, Si: 0.45%, Mn: 0.95%, P: 0.005%, S: 0.002%, Ni: 7.26%, Cr: 16.66%, Al: 0.50%, Mo: 0.40%, Cu: 0.80%, N: 0.02%, Co: 0.21%, and the balance is Fe.
[0080] Comparative Example 1
[0081] The preparation process of Comparative Example 1 is substantially the same as that of Example 1, except that in Comparative Example 1, 0Cr17Ni7Al is used.
[0082] Its chemical composition is C: 0.09%, Si: 0.31%, Mn: 0.8%, P: 0.005%, S: 0.002%, Ni: 7.05%, Cr: 16.70%, Al: 1.00%, Mo: 0.40%, Cu: 0.50%, and the balance is Fe.
[0083] Performance Testing
[0084] The above-mentioned Examples 1-6 and Comparative Example 1 were subjected to performance tests, mainly including the tests of tensile strength and martensite content, and the strength fluctuation value Cv was calculated. The test results are shown in Tables 1-4.
[0085] Table 1 Test results of Example 1
[0086]
[0087]
[0088] Table 2 Test results of Example 2
[0089]
[0090]
[0091] Table 3 Test results of Example 3
[0092]
[0093]
[0094] Table 4 Test results of comparative example 1
[0095]
[0096] The test results of Example 4 are as follows: φ3.5mm-one batch, the cold-drawn strength is above 1550MPa, and the martensite volume fraction is 80%; φ3.5mm-two batches, the cold-drawn strength is above 1520MPa, and the martensite volume fraction is 81%; φ3.5mm-three batches, the cold-drawn strength is above 1530MPa, and the martensite volume fraction is 84%; the strength fluctuation Cv is less than 3%.
[0097] The test results of Example 5 are as follows: φ3.0mm-one batch, the cold-drawn strength is above 1600MPa, and the martensite volume fraction is 86%; φ3.0mm-two batches, the cold-drawn strength is above 1590MPa, and the martensite volume fraction is 85%; φ3.0mm-three batches, the cold-drawn strength is above 1600MPa, and the martensite volume fraction is 85%; the strength fluctuation Cv is less than 3%.
[0098] The test results of Example 6 are as follows: φ0.3mm-one batch, the cold-drawn strength is above 2000MPa, and the martensite volume fraction is 99%; φ0.3mm-two batches, the cold-drawn strength is above 1995MPa, and the martensite volume fraction is 99%; φ0.3mm-three batches, the cold-drawn strength is above 2020MPa, and the martensite volume fraction is 98%; the strength fluctuation Cv is less than 3%.
[0099] Combining Examples 1-3 and Comparative Example 1 and referring to Tables 1-4, it can be seen that the components provided in the embodiments of the present invention are used to prepare three specifications of wires of φ3.5mm, φ3.0mm, and φ0.3mm through multiple rough drawing + finished product drawing. The rough drawing intermediate wire adopts online solution annealing, annealing system 1040℃ insulation 10min, water cooling. The obtained wire not only has high strength, but also has a small strength fluctuation value, and has very good quality consistency and stability; specifically, the tensile strength of φ3.5mm is above 1500MPa, and Cv is less than 2, the tensile strength of φ3.0mm is above 1560MPa, and Cv is less than 2; the tensile strength of φ3.0mm is above 1990MPa, and Cv is less than 3.
[0100] Reference Figure 3-14The metallographic structure is as follows: the structure is martensite (different specifications contain different amounts of retained austenite), no obvious delta ferrite is observed, and the consistency is very good.
[0101] Combined with Example 1 and Comparative Example 1 Figure 1 and 2 After the wire rod was solution treated at 1040℃ for 15min and water cooled, the phase transition point Ms temperature was measured to be 29℃. The microstructure of the wire rod and the comparison with 0Cr17Ni7Al are shown in Figure 2 It can be seen that after the wire rod of the present invention is solution treated, no delta ferrite is observed, the structure is austenite phase + martensite, and the volume fraction of the austenite phase is 68.70%.
[0102] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.
Claims
1. A high-strength controllable phase-change stainless steel wire, characterized in that: Its chemical composition, by weight percentage, includes C≤0.09%, Si≤1.00%, Mn≤1.00%, P≤0.04%, S≤0.030%, Ni: 7.25%~8.00%, Cr: 16.00%~18.00%, Al: 0.50%~0.75%, Mo: 0.20%~0.60%, Cu: 0.50%~1.0%, N: 0.01%~0.10%, Co: 0.10%~0.50%, and the balance is Fe and unavoidable impurities.
2. The high-strength controllable phase-change stainless steel wire according to claim 1, characterized in that: Its chemical composition, by weight percentage, includes C≤0.09%, Si≤1.00%, Mn≤1.00%, P≤0.04%, S≤0.030%, Ni: 7.85%~8.00%, Cr: 16.00%~18.00%, Al: 0.50%~0.65%, Mo: 0.20%~0.60%, Cu: 0.70%~1.0%, N: 0.08%~0.10%, Co: 0.21%~0.50%, and the balance is Fe and unavoidable impurities.
3. The high-strength controllable phase-change stainless steel wire according to claim 1, characterized in that: The martensitic transformation point of the stainless steel wire material ranges from -20°C to 50°C.
4. The high-strength controllable phase-change stainless steel wire according to claim 1, characterized in that: The structure of the stainless steel wire is martensite and retained austenite.
5. The high-strength controllable phase-change stainless steel wire according to claim 4, characterized in that: The volume fraction of martensite is 75% to 100%; the volume fraction of delta ferrite is ≤1%.
6. A method for manufacturing a high-strength controllable phase-change stainless steel wire according to any one of claims 1 to 5, characterized in that: The wire rod is obtained by smelting, forging and rolling; the obtained wire rod is subjected to multiple rough drawing, intermediate annealing and finished product drawing to obtain stainless steel wire; The surface reduction rate of the finished product drawn is 56% to 85%.
7. The method for manufacturing high-strength controllable phase transformation stainless steel wire according to claim 6, characterized in that: The intermediate annealing system is a 950°C to 1050°C solution water cooling treatment.
8. The method for manufacturing high-strength controllable phase transformation stainless steel wire according to claim 7, characterized in that: After solution water cooling treatment at 950℃~1050℃, the volume fraction of austenite is ≥60%.
9. The method for manufacturing high-strength controllable phase transformation stainless steel wire according to claim 6, characterized in that: The specification of the wire material is φ3.5mm, φ3.0mm or φ0.3mm.
10. The method for manufacturing high-strength controllable phase transformation stainless steel wire according to claim 6, characterized in that: The tensile strength of the stainless steel wire is above 1500 MPa, and the strength fluctuation Cv value is less than 3%.